EFEK KINERJA MOTOR BENSIN TERHADAP GAS BUANG - son, Edi (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Emission control is not only used to gather the emission data of the tested vehicles andcompare its standart quality, but the most important is to analize the machine conditionbased on that emission control. Because the emission of the exaust describer the machinework and the vehicle owner should know that over emission is able to increase the use of fuelin effectively, increase the frequency of oil substitution and shortened the interval of eachvehicle treatment. If these condition left in a long time there will be a total damaged on themachine.Keywords: Emission Control